PENGEMBANGAN MODUL IPS PADA MATERI GEJALA ALAM DI INDONESIA DENGAN PENDEKATAN SCIENTIFIC BAGI MAHASISWA PGSD - Vera Yuli Erviana (Profesi Pendidikan Dasar, 2018)
Abstract: This research aims to develop and produce Social Studies module.  The module leaning material is natural phenomena in Indonesia with scientific approach. The module develops for college-students of Elementary School Teacher Education, Ahmad Dahlan University. This research was a Research and Development. The development of the module is based on Analyze, Design, Development, Implementation and Evaluation (ADDIE). Data collection techniques are interviews, product assessment by experts, and college-students response sheets.  The instruments of this research are 1) interview guideline to get preliminary information on the analysis of needs in the Elementary School Teacher Education Program; 2) product assessment sheet which is in the form of assessment sheet by expert judgment and expert input in the FGD, and 3)college-students response sheet to understand the module's practicality. The results of the research show the module’s feasibility by the material and learning experts with an average score of 120, with "very good" criteria. The study of feasibility by media experts obtains an average score of 83, with "very good" criteria. Based on the assessment of 10 college-students obtained n = 87.86%, with the module criteria of "very practical". It can be concluded that the module developed is very feasible, in accordance to the assessment of the experts and college-students response.